Technology Can Save the Environment - Bisong, Peter Bisong; Apologun, Sylvester (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2020)
The environment is fast degrading. Experts believe that in the nearest future, the environment will collapse, if the current rate of degradation continues. One of the main drivers of this degradation is believed to be technology. This has led to the widespread perception of technology as a curse rather than a blessing to the environment and humanity. This work agrees that technology is one of the main causes of environmental problems but disagrees that technology is a curse. Technology in itself is value-neutral; it is its usage that leads to bad or good consequences. It is the contention of these researchers, that technology when well driven could restore the health of the environment. Technology due to its wrong positioning in the past has caused environmental problems. It could be repositioned to foster environmental health in the future. Technology therefore, has the potential, to restore and heal what it has wounded, when properly driven.